Association Between Microscopic Colitis and Parkinson's Disease in a Swedish Population. Issue 8 (25th March 2021) - Kang, Xiaoying; Ploner, Alexander; Roelstraete, Bjorn; Khalili, Hamed; Williams, Dylan M.; Pedersen, Nancy L.; Ludvigsson, Jonas F.; Wirdefeldt, Karin
Abstract: Background: Gastrointestinal inflammation has been linked with Parkinson's disease (PD). Microscopic colitis (MC) is an intestinal inflammatory disease with unknown relationship with PD. Objective: This study aimed to examine the association of MC with PD risk. Methods: In this nationwide matched cohort study in Sweden, PD incidence was compared between 12, 609 patients with histologically confirmed MC and a matched population cohort of 58, 879 MC‐free individuals and a sibling cohort comprising all unaffected siblings of the MC patients (NMC /NSibling  = 6281/12, 351). Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression models. Results: During a mean follow‐up of ~7 years, we identified 449 incident PD diagnoses among the MC patients and the population cohort. Overall, MC was associated with an adjusted HR of 1.76 for PD, but the association attenuated substantially during follow‐up. In the time‐varying effects model, PD hazard was 3.45‐fold (95% CI: 2.42, 4.93) higher during the first 2 years after biopsy and 1.80‐fold (95% CI: 1.23, 2.64) higher during the following 3 years among MC versus MC‐free individuals but was not different beyond 5 years after biopsy (HR: 1.03; 95% CI: 0.68, 1.54). This temporal pattern of MC–PD associations persisted when comparing MC patients to their siblings. In a post hoc case–control analysis, we also detected a strong association between MC and preexisting PD (odds ratio: 3.46; 95% CI: 2.91, 4.12). Conclusions: Our findings suggest that MC may not be a risk factor for PD; instead, it may co‐occur with PD as a comorbidity or develop after a diagnosis of PD. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society